Refugee Migration as a "Wicked Problem": American Controlling, Palliative, and Governance Policies in Global Context. (September 2019) - Raadschelders, Jos C. N.; Larrison, Jennica; Thapar, Aditi V.
Refugee migration is a very visible and growing wicked problem. In this conceptual article, we outline a framework that identifies types of policies, levels of government (in refugee receiving countries), and causes for refugee migration as factors that create this wicked problem. Many refugee migration policies in Northern countries are mainly limited to being controlling at the national level and palliative at the local level. We further highlight a serious lack of true governing policies that address the push factors that drive people away from unpalatable political and/or economic circumstances in their home countries. Focusing solely on refugee policies may be practical but is not productive when the larger environmental context that prompts refugee migration is ignored in the longer term.